Profile of Egyptian pediatrics with COVID-19: insights from healthcare providers in Egypt - Salma ZEl Houchi; Hanaa I. Rady; Iman Iskander; Tamer Abdel Hamid; Salma Abdelrehim Seddik; Amira Aly Hegazy; Ahmed Taha Aboushady; Mohamed Eissa; Sherine Khamis Hussein; Dina Hanoura; Miriam Magdy Aziz; Remon Magdy; et al. (Egyptian Pediatric Association Gazette)
Abstract Background The COVID-19 global pandemic significantly impacted populations of all ages. While initially thought to affect adults predominantly, it became clear that children and adolescents were also susceptible to the virus's effects. This study aims to explore the epidemiological patterns, clinical features, laboratory and radiological characteristics, and outcomes of COVID-19 infection in a group of Egyptian children (≤ 18 years). Methods This observational, cross-sectional study is based on a multicenter questionnaire sent to pediatricians managing COVID-19-infected children, through a convenient sampling approach. The clinical picture and investigations of 253 pediatric cases were included. Results Most cases (42%) occurred in children aged 3–10 years, and a slightly higher incidence in males. Eighty-two percent of the cases presented with fever; most patients had lymphopenia and elevated CRP, 59% and 74%, respectively. The most common CT chest finding (done for 85 patients) was a bilateral ground glass appearance, which appeared in almost 45% of the patients. The disease severity was higher in infants < 1 year. Severe and critical forms of the disease were significantly associated with high ferritin and d-dimer. The severity of the disease varied, with infants under one year of age having the highest percentage of severe and critical cases, with a 15% the mortality rate, when compared to other age groups. Conclusion COVID-19 has a wide clinical spectrum of diseases ranging from asymptomatic to severe and critical. In severe and critical cases, death was more common among those with elevated ferritin and d-dimer levels. Infants are more vulnerable to severe forms of the disease.